1996
DOI: 10.1523/jneurosci.16-04-01538.1996
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific multi-site cingulate cortical, limbic thalamic, and hippocampal neuronal activity during concurrent discriminative approach and avoidance training in rabbits

Abstract: This study assessed the context specificity of learning-related neuronal activity: whether the same physical stimuli would elicit different neuronal responses depending on the learning situation. Neuronal activity was recorded simultaneously in six limbic areas as rabbits learned to approach a spout for water reinforcement after a tone (CS+) and to ignore the spout after a different tone (CS-). The rabbits then received avoidance training in which they learned to prevent a foot-shock by stepping in an activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 20 publications
5
33
0
Order By: Relevance
“…Our preferred view is that dynamic modulation of amygdalar and cingulothalamic neurons by hippocampal and entorhinal cortical neurons can prepare the cingulothalamic neurons to respond to task-relevant cues with context-specific patterns of activation which serve to defeat mnemonic pro-active and retro-active interference (Freeman et al 1996). These activation patterns are the first in a cascade of brain events that terminates in retrieval of context-appropriate behavior and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Our preferred view is that dynamic modulation of amygdalar and cingulothalamic neurons by hippocampal and entorhinal cortical neurons can prepare the cingulothalamic neurons to respond to task-relevant cues with context-specific patterns of activation which serve to defeat mnemonic pro-active and retro-active interference (Freeman et al 1996). These activation patterns are the first in a cascade of brain events that terminates in retrieval of context-appropriate behavior and memory.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that the MD is implicated in the normal functioning of different memory processes, both in rats (Floresco et al, 1999;Freeman et al, 1996;Hunt and Aggleton, 1998a;Hunt and Aggleton, 1998b) and monkeys (Gaffan and Parker, 2000;Tanibuchi and Goldman-Rakic, 2003). In one study, it was actually found that MD neurons fired during the delay period of a working memory task (Tanibuchi and Goldman-Rakic 2003).…”
Section: Functional Considerationsmentioning
confidence: 99%
“…Behavioral studies in rats subjected to MD lesions or electrophysiological recordings from MD showed that a series of cognitive functions, including object recognition (Mumby et al, 1993), working memory (Freeman et al, 1996), planning and prospective coding (Daum and Ackermann, 1994), depended on intact inputs from the MD.…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus plays an additional role in using contextual cues during the encoding of memory (Hirsh, 1974;Honey and Good, 1993;Freeman et al, 1996;Good et al, 1998;Kennedy and Shapiro, 2004;Smith et al, 2004). Although involvement of the hippocampus in the context-specific retrieval of extinction has begun to receive attention, no explicit attempts have been made to elucidate a role for the hippocampus in encoding the context specificity of extinction.…”
Section: Introductionmentioning
confidence: 99%